The singing rooster a Manobo chief emphasizes the Manobo work ethic - Wrigglesworth, Hazel J.; Zacharius, Tigar (Special monograph issue / Linguistic Society of the Philippines, 2009)
A selection of six narrative, as told by four Ilianen Manobo reconteurs, along with a description of the dynamic array of rhetorical devices for enabling the Manobo storyteller to become a master of dramatic entertainment--P. [4] of cover.